OUTCOME IN PATIENTS UNDERGOING ENDOSCOPIC LUMBAR DISCECTOMY FOR PROLAPSED PARA SPINAL INTERVERTEBRAL DISC - Husain, Syed Shahzad; Kamboh, Usman Ahmed; Raza, Asif; Adil, Muhammad; Ashraf, Naveed (Pakistan Journal of Physiology, 2017)
Background: Backache is second most common problem presenting to the primary healthcare providers. Lumbar discectomy has been revolutionized from open conventional discectomy to endoscopic removal. Endoscopic procedures are proving their superiority regarding good outcome, less wound site pain and shorter hospital stay, in Neurosurgery as well. Micro discectomy and Endoscopic discectomy is used only in few centres in Pakistan. This study aimed to share our experience of early surgical outcome endoscopic lumbar discectomy in terms postoperative pain improvement and duration of hospital stay Methods: This prospective study was carried out at Neurosurgery Department, Jinnah Hospital, Lahore from Jan 2014 to Jan 2016. During this period, 35 patients of both sexes, aging between 20 and 60 years, with symptoms and signs of lumbago with sciatica were enrolled. Data was collected on a questionnaire after informed verbal and written consent. Results: A total of 35 patients were operated including 10 males and 25 females. Their age ranged from 20 to 60 years with mean age 33.14±8 years. Majority (32, 91%) of the patients had left side prolapsed paracentral disc, and remaining (3, 9%) had right sided prolapsed disc. Regarding the level of disc 19 (54%) patients had L4-5 while 15 (43%) had L5-S1 and remaining one (2.9%) patients had L3-4 level. The post-op wound site visual analogue score was 1.57±1.1. Twenty-five patients had VAS of 1 (71.4%). Minimum hospital stay was 1 day in 16 (45.75%) patients and maximum was 4 days in 3 (8.6%) patients. Mean hospital stay was 1.83±0.95 days. The only complication encountered was iatrogenic dural tear seen in one patient but with no CSF leak from wound site. No surgical site infections were reported at follow-ups. Conclusion: Endoscopic Lumbar discectomy is a safe procedure with short hospital stay. Keywords: sciatica, prolapsed intervertebral disc, microscopic discectomy, endoscopic discectomy Pak J Physiol 2017;13(2):34–7